The concept of service(s) in recent European Union legal texts: The case of online digital content - Damien Broussolle (Eurostat Review on National Accounts and Macroeconomic Indicators (EURONA), 2021)
This paper addresses adverse consequences of the European Union definition of a "service", especially regarding the Digital Single Market Strategy. After an introduction, the second section analyses through legal texts, its somewhat outdated view, where a "service" covers all intangible items. The third section depicts the new economic approach, based on ownership rights, almost adopted by, among others, the System of National Accounts, where intangible information products are goods. The fourth section studies typical problems, such as the tax discrimination between tangible goods and intangible information goods, mistakenly regarded as services (for example books compared with e-books). As to the provision of "digital content", it results in a contorted contractual treatment of intangible goods. The new approach to a "service" could solve these problems. Overall the paper advocates for more exchanges between economists and law experts.
Keywords: L8; L86; K34; O52; 330; intangible good; service; online digital content; digital strategy